Integrated Chip Technologies for Microwave Photonics - QIAN Guang; QIAN Kun; GU Xiaowen; KONG Yuechan; CHEN Tangsheng (Leida xuebao, 2019)
Microwave photonic integrated chip technology is an important supporting technology of microwave photonic radar. It can not only realize the multifunction of devices, reduce the volume of microwave photonic radar, but also greatly improve the stability and reliability. This paper introduces the photonic integrated chip technologies based on the commonly used InP, Si, LiNbO3 and their heterogeneous integrations and the optoelectronic integration chip technologies for microwave photonics. Finally, the future development trends is discussed.